The role of cholesterol metabolism and various steroid abnormalities in autism spectrum disorders: A hypothesis paper - Gillberg, Christopher (Autism Res, 2017)
Based on evidence from the relevant research literature, we present a hypothesis that there may be a link between cholesterol, vitamin D, and steroid hormones which subsequently impacts on the development of at least some of the “autisms” [Coleman & Gillberg]. Our hypothesis, driven by the peer reviewed literature, posits that there may be links between cholesterol metabolism, which we will refer to as “steroid metabolism” and findings of steroid abnormalities of various kinds (cortisol, testosterone, estrogens, progesterone, vitamin D) in autism spectrum disorder (ASD). Further research investigating these potential links is warranted to further our understanding of the biological mechanisms underlying ASD. Autism Res 2017. © 2017 The Authors Autism Research published by Wiley Periodicals, Inc. on behalf of International Society for Autism Research. Autism Res 2017, 10: 1022–1044. © 2017 International Society for Autism Research, Wiley Periodicals, Inc.